Antibacterial PET coiled material as well as preparation method and application thereof
By adding specific compatibility agents and modified composite antibacterial agents to the PET coil, the problem of PET coil lacking antibacterial ability in certain application scenarios is solved, and the stable antibacterial performance and good mechanical properties of PET coil are achieved.
Patent Information
- Application Number
- CN202411948597.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
Existing PET coils lack significant antibacterial ability in some application scenarios (such as food packaging), and traditional methods to enhance antibacterial properties have the problem that the antibacterial effect will weaken over time.
By adding specific compatibility agents to the PET matrix with modified composite antibacterial agents, including ethylene-methyl acrylate-glycidyl methacrylate random terpolymers, modified porous zinc oxide, catechin gallate and ε-polylysine hydrochloride, to form a stable complex to improve the antibacterial properties of the PET coil.
The excellent antibacterial properties of PET coils are achieved and good mechanical properties are maintained, such as bending strength and impact resistance, avoiding the problem of the decreasing effect of traditional antibacterial materials over time.
Smart Images

Figure BDA0005214304410000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an antibacterial PET coil and a preparation method and application thereof. Background Art
[0002] Polyethylene terephthalate (PET for short) is a highly crystalline polymer synthesized from ethylene terephthalate through a dehydration condensation reaction. PET has a smooth and glossy surface, excellent physical and mechanical properties, and a wide range of applicable temperatures. PET also has excellent creep resistance, fatigue resistance, friction resistance, and dimensional stability, which make it widely used in many fields. PET coils are often used in packaging materials, films, fibers, and engineering plastics, especially in food packaging, beverage bottles, electronic device protection, and textiles. Its high chemical resistance and mechanical strength enable PET coils to maintain stable performance in various harsh environments and meet different application requirements. In addition, the recyclability of PET coils also makes it one of the first choices for environmentally friendly materials, helping to reduce environmental pollution and waste of resources.
[0003] As a widely used plastic, PET occupies an important position in many fields such as food packaging, beverage containers, textiles, etc., mainly due to its excellent mechanical strength, transparency, and chemical corrosion resistance. However, in certain specific application scenarios (such as food packaging), in addition to requiring PET coils to have basic physical and chemical properties, they are also required to have additional functions, such as antibacterial and waterproof properties, to ensure food safety and extend shelf life. PET itself does not have significant antibacterial ability. The current methods to enhance the antibacterial properties of PET mainly include adding antibacterial agents to PET, using surface coating technology, or blending and modifying with other materials.
[0004] The above methods can improve the antibacterial properties of PET coils to a certain extent, but they also have certain limitations. For example, the antibacterial effect weakens over time. This is mainly because the antibacterial components may seep out of the PET material, resulting in reduced antibacterial efficiency. Therefore, providing a PET coil that not only has good basic properties such as mechanics but also has stable antibacterial properties is an urgent problem to be solved by the present invention. Summary of the invention
[0005] The purpose of the present invention is to provide an antibacterial PET coil, which not only has excellent antibacterial properties but also has good mechanical properties such as bending strength and impact strength by adding a specific compatibilizer and a modified composite antibacterial agent into a PET matrix.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides an antibacterial PET coil, comprising the following raw materials in parts by weight:
[0008] 110-130 parts by weight of PET (polyethylene terephthalate), 2-4 parts by weight of nano titanium dioxide, 1-3 parts by weight of nano talc, 4-6 parts by weight of compatibilizer, 1-2 parts by weight of antioxidant, 1-2 parts by weight of lubricant, and 6-8 parts by weight of modified composite antibacterial agent.
[0009] Preferably, the compatibilizer is an ethylene-methyl acrylate-glycidyl methacrylate random terpolymer and / or an ethylene-acrylate-maleic anhydride random terpolymer.
[0010] Furthermore, the compatibilizer is a mixture of ethylene-methyl acrylate-glycidyl methacrylate random terpolymer and ethylene-acrylate-maleic anhydride random terpolymer in a weight ratio of 1-2:1.
[0011] The present invention adopts specific ethylene-methyl acrylate-glycidyl methacrylate random terpolymer and / or ethylene-acrylate-maleic anhydride random terpolymer as compatibilizers. These compatibilizers effectively enhance the interface bonding and compatibility between the PET resin and each component by adjusting the interface interaction and phase morphology of each incompatible component, thereby significantly improving the impact resistance of the PET coil. Specifically, the two work together to promote phase adhesion and increase interface thickness, producing a super-toughening effect that shows incomplete fracture in impact tests. This is because the improved interface adhesion and the formed semi-continuous microstructure can effectively dissipate impact energy. In addition, the combined use of nucleating agents nano-titanium dioxide and nano-talc not only accelerates the crystallization rate of PET and reduces the molding temperature, but also enhances the viscosity and mechanical properties of the material, while improving the surface gloss of the product; the presence of the compatibilizer effectively reduces the interfacial tension between molecules of other raw materials during the mixing process, and enhances the interfacial adhesion, which helps to form a more uniform and stable dispersed phase and continuous phase structure, ultimately achieving the purpose of improving the strength and impact resistance of the coil; the synergistic effect of the entire process ensures the good rheology of the material during processing, providing a reliable guarantee for the preparation of high-performance PET coils.
[0012] Preferably, the preparation method of the modified composite antibacterial agent comprises the following steps:
[0013] 1.5-2 parts by weight of zinc acetate and 3-3.5 parts by weight of urea are added into water and ultrasonically dispersed for 10-20 minutes, and then 0.2-0.4 parts by weight of polyethylene glycol 400 and 0.3-0.5 parts by weight of Tween 60 are added and stirred for 80-100 minutes, and then placed in a high-pressure reactor, heated to react for 7-10 hours, cooled, centrifuged and dried to obtain material I, and material I is placed in a muffle furnace and calcined for 130-160 minutes, and cooled with the furnace to obtain porous zinc oxide;
[0014] 0.6-0.9 parts by weight of porous zinc oxide is added to N,N-dimethylformamide and mixed evenly, and then 0.04-0.06 parts by weight of isopropyl tri(dodecylbenzenesulfonyl) titanate and 0.02-0.04 parts by weight of isopropyl tri(dioctylphosphoyl) titanate are added, heated and stirred for 60-70 minutes, centrifuged and dried to obtain modified porous zinc oxide;
[0015] 0.02-0.03 parts by weight of catechin gallate and 0.02-0.03 parts by weight of ε-polylysine hydrochloride are added to an ethanol aqueous solution and mixed evenly, and then 0.5-0.7 parts by weight of modified porous zinc oxide is added and stirred for 2-4 hours, centrifuged and dried to obtain a modified composite antibacterial agent.
[0016] The present invention effectively improves the antibacterial performance of the PET coil by using a homemade modified composite antibacterial agent, and maintains excellent stability, avoiding the problem that the antibacterial effect of traditional antibacterial materials decreases significantly over time. The modified composite antibacterial agent is composed of biological antibacterial agents catechin gallate, ε-polylysine hydrochloride and modified porous zinc oxide; in the preparation process of porous zinc oxide, by adding polyethylene glycol 400 and Tween 60 as dispersants and pore-forming agents, a porous structure is successfully constructed on the surface of zinc oxide. These porous structures greatly increase the specific surface area of zinc oxide, and also give the material better stability and surface permeability, which provides an ideal carrier for the subsequent loading of biological antibacterial agents; subsequently, isopropyl tri(dodecylbenzenesulfonyl) titanate and isopropyl tri(dioctylphosphoyloxy) titanate are used to modify the surface of porous zinc oxide. These two titanates can not only enhance the chemical stability of porous zinc oxide, but also enhance the chemical stability of porous zinc oxide. , and can also improve its affinity with the biological antibacterial agent, so that the antibacterial agent can be firmly fixed on the surface and pores of porous zinc oxide by chemical bonds; catechin gallate and ε-polylysine hydrochloride as biological antibacterial agents have broad-spectrum antibacterial activity, can destroy bacterial cell walls, and inhibit bacterial growth and reproduction. When these two antibacterial agents are combined with modified porous zinc oxide to form a complex, due to the antibacterial properties of porous zinc oxide itself and the synergistic effect formed with the biological antibacterial agent, the complex shows a stronger antibacterial effect; More importantly, the antibacterial agent is fixed on the porous zinc oxide by chemical bonds, which greatly reduces its migration in the PET matrix and ensures the durability and stability of the antibacterial performance. In addition, the complex formed by modified porous zinc oxide and the biological antibacterial agent has good dispersibility and compatibility, and can be evenly distributed in the PET matrix, which not only improves the overall antibacterial properties of the PET coil, but also avoids the adverse effects on the mechanical properties.
[0017] Furthermore, the preparation method of the modified composite antibacterial agent comprises the following steps:
[0018] 1.5-2 parts by weight of zinc acetate and 3-3.5 parts by weight of urea are added to 150-200 parts by weight of water for ultrasonic dispersion for 10-20 minutes, the ultrasonic frequency is 20-30kHz, and the ultrasonic power is 100-200W, then 0.2-0.4 parts by weight of polyethylene glycol 400 and 0.3-0.5 parts by weight of Tween 60 are added, and stirred at 23-27°C and 100-200rpm for 80-100 minutes, and then placed in a high-pressure reactor, reacted at 130-140°C for 7-10 hours, cooled to room temperature, centrifuged and dried to obtain material I, and material I is placed in a muffle furnace, calcined at 400-500°C for 130-160 minutes, and cooled to room temperature with the furnace to obtain porous zinc oxide;
[0019] 0.6-0.9 parts by weight of porous zinc oxide is added to 30-50 parts by weight of N,N-dimethylformamide and mixed evenly, and then 0.04-0.06 parts by weight of isopropyl tri(dodecylbenzenesulfonyl) titanate and 0.02-0.04 parts by weight of isopropyl tri(dioctylphosphoyl) titanate are added, and the mixture is stirred at 45-55° C. and 100-200 rpm for 60-70 min, centrifuged and dried to obtain modified porous zinc oxide;
[0020] 0.02-0.03 parts by weight of catechin gallate and 0.02-0.03 parts by weight of ε-polylysine hydrochloride are added to 15-30 parts by weight of 70-80wt% ethanol aqueous solution and mixed evenly, then 0.5-0.7 parts by weight of modified porous zinc oxide are added, stirred at 23-27°C and 100-200rpm for 2-4h, centrifuged and dried to obtain a modified composite antibacterial agent.
[0021] Preferably, the antioxidant is one or a mixture of two of the antioxidant 1076, antioxidant 1010, antioxidant 168, antioxidant 616, and antioxidant DSTDP.
[0022] Furthermore, the antioxidant is a mixture of antioxidant 1076 and antioxidant 168 in a weight ratio of 1-3:1.
[0023] Preferably, the lubricant is one or a mixture of two of pentaerythritol stearate, erucamide, polyethylene wax, polyvinyl alcohol, and ethylene bisstearamide.
[0024] Furthermore, the lubricant is a mixture of pentaerythritol stearate and erucamide in a weight ratio of 3-5:5.
[0025] Preferably, the average particle size of the nano titanium dioxide is 50-60 nm.
[0026] Preferably, the average particle size of the nano talc is 180-200 nm.
[0027] The present invention provides a method for preparing an antibacterial PET coil, comprising the following steps:
[0028] According to the raw material formula, PET, nano titanium dioxide, nano talc, compatibilizer, antioxidant, lubricant and modified composite antibacterial agent are weighed, the weighed raw materials are added into a high-speed mixer and mixed for 8-12 minutes at a stirring speed of 200-350 rpm, and then added into an extruder for extrusion molding at an extrusion temperature of 260-275°C and a screw speed of 20-40 rpm, and finally the antibacterial PET coil is obtained through calendering, pulling, cutting and winding processes.
[0029] Application of the above antibacterial PET coil in the preparation of packaging materials.
[0030] The applications include but are not limited to dumpling packaging boxes, raw meat packaging boxes, lunch boxes, trays, and cup lids.
[0031] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0032] 1. The present invention provides a method for preparing an antibacterial PET coil, by adding a specific compatibilizer and a modified composite antibacterial agent into a PET matrix, wherein the compatibilizer is an ethylene-methyl acrylate-glycidyl methacrylate random terpolymer and / or an ethylene-acrylate-maleic anhydride random terpolymer, and the modified composite antibacterial agent is prepared from catechin gallate, ε-polylysine hydrochloride and modified porous zinc oxide, so that the PET coil has not only excellent antibacterial performance, but also good mechanical properties such as bending strength and impact strength, and can be widely used in packaging materials such as packaging boxes, lunch boxes, cup lids, trays, etc., and the preparation method is simple.
[0033] 2. The present invention uses ethylene-methyl acrylate-glycidyl methacrylate random terpolymer and / or ethylene-acrylate-maleic anhydride random terpolymer as compatibilizers, and the two act synergistically to effectively enhance the interface bonding and compatibility between the PET resin and each component by adjusting the interface interaction and phase morphology of each incompatible component, thereby significantly improving the impact resistance of the PET coil. In addition, by using the nucleating agent nano titanium dioxide and nano talc, not only the crystallization rate of PET is accelerated, the molding temperature is reduced, the viscosity and mechanical properties of the material are enhanced, and the surface gloss of the product is improved.
[0034] 3. The present invention effectively improves the antibacterial performance of the PET coil by adding a homemade modified composite antibacterial agent, and maintains excellent stability, avoiding the problem that the antibacterial effect of traditional antibacterial materials decreases significantly over time. The modified composite antibacterial agent is composed of a biological antibacterial agent catechin gallate, ε-polylysine hydrochloride and modified porous zinc oxide. The composite formed by the modified porous zinc oxide and the biological antibacterial agent has good dispersibility and compatibility, and can be evenly distributed in the PET matrix, which not only improves the overall antibacterial performance of the PET coil, but also avoids the adverse effect on the mechanical properties. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] PET, brand: FR530 NC010, melt volume flow rate (280℃ / 2.16kg, ISO1133) is 6.0cm 3 / 10min, Manufacturer: DuPont, USA.
[0037] Ethylene-methyl acrylate-glycidyl methacrylate random terpolymer, brand: EPA-810, melt mass flow rate (190℃ / 2.16kg, ISO1133) is 10g / 10min, grafting rate is 5%, manufacturer: Hangzhou Haiyi Polymer Materials Co., Ltd.
[0038] Ethylene-acrylate-maleic anhydride random terpolymer, brand: 4700, melt mass flow rate (190℃ / 2.16kg, ISO1133) is 7.0g / 10min, grafting rate is 1.3%, manufacturer: Arkema.
[0039] Example 1
[0040] This embodiment provides an antibacterial PET coil, comprising the following raw materials in parts by weight:
[0041] 110 parts by weight of PET, 2 parts by weight of nano titanium dioxide, 1 part by weight of nano talc, 4 parts by weight of compatibilizer, 1 part by weight of antioxidant, 1 part by weight of lubricant, and 6 parts by weight of modified composite antibacterial agent. The compatibilizer is a mixture of ethylene-methyl acrylate-glycidyl methacrylate random terpolymer and ethylene-acrylate-maleic anhydride random terpolymer in a weight ratio of 1:1. The antioxidant is a mixture of antioxidant 1076 and antioxidant 168 in a weight ratio of 1:1. The lubricant is a mixture of pentaerythritol stearate and erucamide in a weight ratio of 3:5.
[0042] The preparation method of the modified composite antibacterial agent comprises the following steps:
[0043] 1.65 parts by weight of zinc acetate and 3.25 parts by weight of urea were added to 180 parts by weight of water and ultrasonically dispersed for 15 minutes, with an ultrasonic frequency of 20 kHz and an ultrasonic power of 150 W, and then 0.3 parts by weight of polyethylene glycol 400 and 0.4 parts by weight of Tween 60 were added, stirred at 25° C. and 150 rpm for 90 minutes, and then placed in a high-pressure reactor, reacted at 135° C. for 8 hours, cooled to room temperature, centrifuged and dried to obtain material I, and material I was placed in a muffle furnace, calcined at 450° C. for 150 minutes, and cooled to room temperature with the furnace to obtain porous zinc oxide;
[0044] 0.75 parts by weight of porous zinc oxide was added to 40 parts by weight of N,N-dimethylformamide and mixed evenly, and then 0.05 parts by weight of isopropyl tri(dodecylbenzenesulfonyl) titanate and 0.03 parts by weight of isopropyl tri(dioctylphosphoyl) titanate were added, and the mixture was stirred at 50° C. and 150 rpm for 65 min, centrifuged and dried to obtain modified porous zinc oxide;
[0045] 0.025 parts by weight of catechin gallate and 0.025 parts by weight of ε-polylysine hydrochloride were added to 20 parts by weight of 75wt% ethanol aqueous solution and mixed evenly, and then 0.6 parts by weight of modified porous zinc oxide was added, stirred at 25°C and 150rpm for 3h, centrifuged and dried to obtain a modified composite antibacterial agent.
[0046] This embodiment provides a method for preparing an antibacterial PET coil, comprising the following steps:
[0047] According to the raw material formula, PET, nano titanium dioxide, nano talc, compatibilizer, antioxidant, lubricant and modified composite antibacterial agent are weighed, the weighed raw materials are added to a high-speed mixer and mixed for 8 minutes at a stirring speed of 200 rpm, and then added to an extruder for extrusion molding at an extrusion temperature of 260°C and a screw speed of 20 rpm, and finally the antibacterial PET coil is obtained through calendering, pulling, cutting and winding processes.
[0048] Example 2
[0049] This embodiment provides an antibacterial PET coil, comprising the following raw materials in parts by weight: 120 parts by weight of PET, 3 parts by weight of nano titanium dioxide, 2 parts by weight of nano talc, 5 parts by weight of compatibilizer, 1.5 parts by weight of antioxidant, 1.5 parts by weight of lubricant, and 7 parts by weight of modified composite antibacterial agent. The compatibilizer is a mixture of ethylene-methyl acrylate-glycidyl methacrylate random terpolymer and ethylene-acrylate-maleic anhydride random terpolymer in a weight ratio of 1.5:1. The antioxidant is a mixture of antioxidant 1076 and antioxidant 168 in a weight ratio of 2:1. The lubricant is a mixture of pentaerythritol stearate and erucamide in a weight ratio of 4:5.
[0050] The preparation method of the modified composite antibacterial agent is the same as that in Example 1.
[0051] This embodiment provides a method for preparing an antibacterial PET coil, comprising the following steps:
[0052] According to the raw material formula, PET, nano titanium dioxide, nano talc, compatibilizer, antioxidant, lubricant and modified composite antibacterial agent are weighed, the weighed raw materials are added to a high-speed mixer and mixed for 10 minutes at a stirring speed of 300 rpm, and then added to an extruder for extrusion molding at an extrusion temperature of 270°C and a screw speed of 30 rpm, and finally the antibacterial PET coil is obtained through calendering, pulling, cutting and winding processes.
[0053] Example 3
[0054] This embodiment provides an antibacterial PET coil, comprising the following raw materials in parts by weight:
[0055] 130 parts by weight of PET, 4 parts by weight of nano titanium dioxide, 3 parts by weight of nano talc, 6 parts by weight of compatibilizer, 2 parts by weight of antioxidant, 2 parts by weight of lubricant, and 8 parts by weight of modified composite antibacterial agent. The compatibilizer is a mixture of ethylene-methyl acrylate-glycidyl methacrylate random terpolymer and ethylene-acrylate-maleic anhydride random terpolymer in a weight ratio of 2:1. The antioxidant is a mixture of antioxidant 1076 and antioxidant 168 in a weight ratio of 3:1. The lubricant is a mixture of pentaerythritol stearate and erucamide in a weight ratio of 5:5.
[0056] The preparation method of the modified composite antibacterial agent is the same as that in Example 1.
[0057] This embodiment provides a method for preparing an antibacterial PET coil, comprising the following steps:
[0058] According to the raw material formula, PET, nano titanium dioxide, nano talc, compatibilizer, antioxidant, lubricant and modified composite antibacterial agent are weighed, the weighed raw materials are added to a high-speed mixer and mixed for 12 minutes at a stirring speed of 350 rpm, and then added to an extruder for extrusion molding at an extrusion temperature of 275°C and a screw speed of 40 rpm, and finally the antibacterial PET coil is obtained through calendering, pulling, cutting and winding processes.
[0059] Comparative Example 1
[0060] The difference between this comparative example and Example 2 is that the compatibilizer is a random terpolymer of ethylene-methyl acrylate-glycidyl methacrylate.
[0061] Comparative Example 2
[0062] The difference between this comparative example and Example 2 is that the compatibilizer is a random terpolymer of ethylene-acrylate-maleic anhydride.
[0063] Comparative Example 3
[0064] The difference between this comparative example and Example 2 is that the preparation method of the modified composite antibacterial agent is different, which is as follows: The preparation method of the modified composite antibacterial agent comprises the following steps:
[0065] 0.75 parts by weight of commercially available nano zinc oxide (average particle size of 50-80 nm) was added to 40 parts by weight of N,N-dimethylformamide and mixed evenly, and then 0.05 parts by weight of isopropyl tri(dodecylbenzenesulfonyl) titanate and 0.03 parts by weight of isopropyl tri(dioctylphosphoyl) titanate were added, and the mixture was stirred at 50° C. and 150 rpm for 65 min, centrifuged and dried to obtain modified zinc oxide;
[0066] 0.025 parts by weight of catechin gallate and 0.025 parts by weight of ε-polylysine hydrochloride were added to 20 parts by weight of 75wt% ethanol aqueous solution and mixed evenly, then 0.6 parts by weight of modified zinc oxide was added, stirred at 25°C and 150rpm for 3h, centrifuged and dried to obtain a modified composite antibacterial agent.
[0067] Comparative Example 4
[0068] The difference between this comparative example and Example 2 is that the preparation method of the modified composite antibacterial agent is different, which is as follows: The preparation method of the modified composite antibacterial agent comprises the following steps:
[0069] 1.65 parts by weight of zinc acetate and 3.25 parts by weight of urea were added to 180 parts by weight of water and ultrasonically dispersed for 15 minutes, with an ultrasonic frequency of 20 kHz and an ultrasonic power of 150 W, and then 0.3 parts by weight of polyethylene glycol 400 and 0.4 parts by weight of Tween 60 were added, stirred at 25° C. and 150 rpm for 90 minutes, and then placed in a high-pressure reactor, reacted at 135° C. for 8 hours, cooled to room temperature, centrifuged and dried to obtain material I, and material I was placed in a muffle furnace, calcined at 450° C. for 150 minutes, and cooled to room temperature with the furnace to obtain porous zinc oxide;
[0070] 0.025 parts by weight of catechin gallate and 0.025 parts by weight of ε-polylysine hydrochloride were added to 20 parts by weight of 75wt% ethanol aqueous solution and mixed evenly, and then 0.6 parts by weight of porous zinc oxide was added, stirred at 25°C and 150rpm for 3h, centrifuged and dried to obtain a modified composite antibacterial agent.
[0071] Comparative Example 5
[0072] The difference between this comparative example and Example 2 is that the preparation method of the modified composite antibacterial agent is different, which is as follows: The preparation method of the modified composite antibacterial agent comprises the following steps:
[0073] 1.65 parts by weight of zinc acetate and 3.25 parts by weight of urea are added to 180 parts by weight of water and ultrasonically dispersed for 15 minutes, with an ultrasonic frequency of 20 kHz and an ultrasonic power of 150 W, and then 0.7 parts by weight of Tween 60 are added, stirred at 25° C. and 150 rpm for 90 minutes, and then placed in a high-pressure reactor, reacted at 135° C. for 8 hours, cooled to room temperature, centrifuged and dried to obtain material I, and material I is placed in a muffle furnace, calcined at 450° C. for 150 minutes, and cooled to room temperature with the furnace to obtain porous zinc oxide;
[0074] 0.75 parts by weight of porous zinc oxide was added to 40 parts by weight of N,N-dimethylformamide and mixed evenly, and then 0.05 parts by weight of isopropyl tri(dodecylbenzenesulfonyl) titanate and 0.03 parts by weight of isopropyl tri(dioctylphosphoyl) titanate were added, and the mixture was stirred at 50° C. and 150 rpm for 65 min, centrifuged and dried to obtain modified porous zinc oxide;
[0075] 0.025 parts by weight of catechin gallate and 0.025 parts by weight of ε-polylysine hydrochloride were added to 20 parts by weight of 75wt% ethanol aqueous solution and mixed evenly, and then 0.6 parts by weight of modified porous zinc oxide was added, stirred at 25°C and 150rpm for 3h, centrifuged and dried to obtain a modified composite antibacterial agent.
[0076] Comparative Example 6
[0077] The difference between this comparative example and Example 2 is that the preparation method of the modified composite antibacterial agent is different, which is as follows: The preparation method of the modified composite antibacterial agent comprises the following steps:
[0078] 1.65 parts by weight of zinc acetate and 3.25 parts by weight of urea were added to 180 parts by weight of water and ultrasonically dispersed for 15 minutes, with an ultrasonic frequency of 20 kHz and an ultrasonic power of 150 W, and then 0.3 parts by weight of polyethylene glycol 400 and 0.4 parts by weight of Tween 60 were added, stirred at 25° C. and 150 rpm for 90 minutes, and then placed in a high-pressure reactor, reacted at 135° C. for 8 hours, cooled to room temperature, centrifuged and dried to obtain material I, and material I was placed in a muffle furnace, calcined at 450° C. for 150 minutes, and cooled to room temperature with the furnace to obtain porous zinc oxide;
[0079] 0.75 parts by weight of porous zinc oxide was added to 40 parts by weight of N,N-dimethylformamide and mixed evenly, and then 0.05 parts by weight of isopropyl tri(dodecylbenzenesulfonyl) titanate and 0.03 parts by weight of isopropyl tri(dioctylphosphoyl) titanate were added, and the mixture was stirred at 50° C. and 150 rpm for 65 min, centrifuged and dried to obtain modified porous zinc oxide;
[0080] 0.05 parts by weight of ε-polylysine hydrochloride was added to 20 parts by weight of 75wt% ethanol aqueous solution and mixed evenly, then 0.6 parts by weight of modified porous zinc oxide was added, stirred at 25°C and 150rpm for 3h, centrifuged and dried to obtain a modified composite antibacterial agent.
[0081] Comparative Example 7
[0082] The difference between this comparative example and Example 2 is that the preparation method of the modified composite antibacterial agent is different, which is as follows: The preparation method of the modified composite antibacterial agent comprises the following steps:
[0083] 1.65 parts by weight of zinc acetate and 3.25 parts by weight of urea were added to 180 parts by weight of water and ultrasonically dispersed for 15 minutes, with an ultrasonic frequency of 20 kHz and an ultrasonic power of 150 W, and then 0.3 parts by weight of polyethylene glycol 400 and 0.4 parts by weight of Tween 60 were added, stirred at 25° C. and 150 rpm for 90 minutes, and then placed in a high-pressure reactor, reacted at 135° C. for 8 hours, cooled to room temperature, centrifuged and dried to obtain material I, and material I was placed in a muffle furnace, calcined at 450° C. for 150 minutes, and cooled to room temperature with the furnace to obtain porous zinc oxide;
[0084] 0.75 parts by weight of porous zinc oxide was added to 40 parts by weight of N,N-dimethylformamide and mixed evenly, and then 0.05 parts by weight of isopropyl tri(dodecylbenzenesulfonyl) titanate and 0.03 parts by weight of isopropyl tri(dioctylphosphoyl) titanate were added, and the mixture was stirred at 50° C. and 150 rpm for 65 min, centrifuged and dried to obtain modified porous zinc oxide;
[0085] 0.05 parts by weight of catechin gallate was added to 20 parts by weight of 75wt% ethanol aqueous solution and mixed evenly, then 0.6 parts by weight of modified porous zinc oxide was added, stirred at 25°C and 150rpm for 3h, centrifuged and dried to obtain a modified composite antibacterial agent.
[0086] Performance Testing
[0087] 1. The mechanical properties of the antibacterial PET coils prepared in the above Examples 1-3 and Comparative Examples 1-4 were tested. The bending strength was measured according to the standard GB / T 9341-2008, the sample size was 80×10×4 mm, 5 groups were paralleled, and the average value was taken. The cantilever beam impact strength was measured according to the standard GB / T1843-2008, type A sample, 5 groups were paralleled, and the average value was taken. The results are shown in Table 1.
[0088] Table 1. Mechanical properties test results
[0089] Bending strength / MPa <![CDATA[Impact strength / (kJ·m -2 )]]> Example 1 208.3 50.5 Example 2 210.5 51.8 Example 3 211.7 52.6 Comparative Example 1 205.1 48.3 Comparative Example 2 203.0 47.2 Comparative Example 3 200.7 45.0 Comparative Example 4 202.2 46.8
[0090] 2. The antibacterial performance of the antibacterial PET coils prepared in the above Examples 1-3 and Comparative Examples 3-7 was tested. The antibacterial rate refers to the standard GB / T 31402-2023, and the test bacteria are: Escherichia coli ATCC 8739, Staphylococcus aureus ATCC6538P. The test conditions are: the above antibacterial PET coils are placed in 50°C water and kept at a constant temperature for 60 hours, and then taken out and dried before testing. Each sample was tested in 10 groups and the average value was taken. The results are shown in Table 2.
[0091] Table 2. Antibacterial performance test results
[0092]
[0093] It can be seen from the above performance test results that the PET coils prepared in Examples 1-3 have good bending performance, impact resistance and antibacterial performance, especially the comprehensive performance of the PET coil of Example 2 is the most outstanding. This is because the present invention adopts a compatibilizer composed of an ethylene-methyl acrylate-glycidyl methacrylate random terpolymer and an ethylene-acrylate-maleic anhydride random terpolymer, and the two act synergistically to adjust the interfacial interaction and phase morphology of the incompatible components, thereby effectively enhancing the interface bonding and compatibility between the PET resin and the components, thereby significantly improving the impact resistance of the PET coil; a specific modified composite antibacterial agent is also added to effectively improve the antibacterial performance of the PET coil, and the antibacterial performance is long-lasting and stable.
[0094] In comparison, since Comparative Examples 1-7 did not adopt the necessary technical solutions, the corresponding performance tests were significantly worse than those of Examples 1-3. In Comparative Examples 1-2, a compatibilizer composed of a random terpolymer of ethylene-methyl acrylate-glycidyl methacrylate and a random terpolymer of ethylene-acrylate-maleic anhydride was not used, and in Comparative Examples 3-7, a modified composite antibacterial agent prepared by a specific method was not used. From the results, it can be seen that the impact resistance and antibacterial stability of the PET coil are reduced. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0095] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An antibacterial PET coil, characterized in that: It includes the following raw materials in parts by weight: 110-130 parts by weight of PET, 2-4 parts by weight of nano titanium dioxide, 1-3 parts by weight of nano talc, 4-6 parts by weight of a compatibilizer, 1-2 parts by weight of an antioxidant, 1-2 parts by weight of a lubricant, and 6-8 parts by weight of a modified composite antibacterial agent; the compatibilizer is a random terpolymer of ethylene-methyl acrylate-glycidyl methacrylate and / or a random terpolymer of ethylene-acrylate-maleic anhydride.
2. The antibacterial PET coil according to claim 1, characterized in that: The preparation method of the modified composite antibacterial agent comprises the following steps: 1.5-2 parts by weight of zinc acetate and 3-3.5 parts by weight of urea are added into water and ultrasonically dispersed for 10-20 minutes, and then 0.2-0.4 parts by weight of polyethylene glycol 400 and 0.3-0.5 parts by weight of Tween 60 are added and stirred for 80-100 minutes, and then placed in a high-pressure reactor, heated to react for 7-10 hours, cooled, centrifuged and dried to obtain material I, and material I is placed in a muffle furnace and calcined for 130-160 minutes, and cooled with the furnace to obtain porous zinc oxide; 0.6-0.9 parts by weight of porous zinc oxide is added to N,N-dimethylformamide and mixed evenly, and then 0.04-0.06 parts by weight of isopropyl tri(dodecylbenzenesulfonyl) titanate and 0.02-0.04 parts by weight of isopropyl tri(dioctylphosphoyl) titanate are added, heated and stirred for 60-70 minutes, centrifuged and dried to obtain modified porous zinc oxide; 0.02-0.03 parts by weight of catechin gallate and 0.02-0.03 parts by weight of ε-polylysine hydrochloride are added to an ethanol aqueous solution and mixed evenly, and then 0.5-0.7 parts by weight of modified porous zinc oxide is added and stirred for 2-4 hours, centrifuged and dried to obtain a modified composite antibacterial agent.
3. The antibacterial PET coil according to claim 2, characterized in that: The preparation method of the modified composite antibacterial agent comprises the following steps: 1.5-2 parts by weight of zinc acetate and 3-3.5 parts by weight of urea are added to 150-200 parts by weight of water for ultrasonic dispersion for 10-20 minutes, the ultrasonic frequency is 20-30kHz, and the ultrasonic power is 100-200W, then 0.2-0.4 parts by weight of polyethylene glycol 400 and 0.3-0.5 parts by weight of Tween 60 are added, and stirred at 23-27°C and 100-200rpm for 80-100 minutes, and then placed in a high-pressure reactor, reacted at 130-140°C for 7-10 hours, cooled to room temperature, centrifuged and dried to obtain material I, and material I is placed in a muffle furnace, calcined at 400-500°C for 130-160 minutes, and cooled to room temperature with the furnace to obtain porous zinc oxide; 0.6-0.9 parts by weight of porous zinc oxide is added to 30-50 parts by weight of N,N-dimethylformamide and mixed evenly, and then 0.04-0.06 parts by weight of isopropyl tri(dodecylbenzenesulfonyl) titanate and 0.02-0.04 parts by weight of isopropyl tri(dioctylphosphoyl) titanate are added, and the mixture is stirred at 45-55° C. and 100-200 rpm for 60-70 min, centrifuged and dried to obtain modified porous zinc oxide; 0.02-0.03 parts by weight of catechin gallate and 0.02-0.03 parts by weight of ε-polylysine hydrochloride are added to 15-30 parts by weight of 70-80wt% ethanol aqueous solution and mixed evenly, then 0.5-0.7 parts by weight of modified porous zinc oxide are added, stirred at 23-27°C and 100-200rpm for 2-4h, centrifuged and dried to obtain a modified composite antibacterial agent.
4. The antibacterial PET coil according to claim 1, characterized in that: The compatibilizer is a mixture of ethylene-methyl acrylate-glycidyl methacrylate random terpolymer and ethylene-acrylate-maleic anhydride random terpolymer in a weight ratio of 1-2:
1.
5. The antibacterial PET coil according to claim 1, characterized in that: The antioxidant is one or a mixture of two of the antioxidant 1076, antioxidant 1010, antioxidant 168, antioxidant 616, and antioxidant DSTDP.
6. The antibacterial PET coil according to claim 5, characterized in that: The antioxidant is a mixture of antioxidant 1076 and antioxidant 168 in a weight ratio of 1-3:
1.
7. The antibacterial PET coil according to claim 1, characterized in that: The lubricant is one or a mixture of two of pentaerythritol stearate, erucic acid amide, polyethylene wax, polyvinyl alcohol, and ethylene bisstearamide.
8. The antibacterial PET coil according to claim 7, characterized in that: The lubricant is a mixture of pentaerythritol stearate and erucamide in a weight ratio of 3-5:
5.
9. The method for preparing the antibacterial PET coil according to any one of claims 1 to 8, characterized in that: The steps include: According to the raw material formula, PET, nano titanium dioxide, nano talc, compatibilizer, antioxidant, lubricant and modified composite antibacterial agent are weighed, the weighed raw materials are added into a high-speed mixer and mixed for 8-12 minutes at a stirring speed of 200-350 rpm, and then added into an extruder for extrusion molding at an extrusion temperature of 260-275°C and a screw speed of 20-40 rpm, and finally the antibacterial PET coil is obtained through calendering, pulling, cutting and winding processes.
10. Use of the antibacterial PET coil according to any one of claims 1 to 8 in the preparation of packaging materials.
Citation Information
Cited By
Grease-resistant food-grade TPE (Thermoplastic Elastomer) inner pad material and preparation method thereof
CN120535874A